Impact of Government Effectiveness on Economic Growth in Latin America - Šestov, Anatolij (2025)
This thesis examines the relationship between government quality and economic growth in Latin America, testing the hypothesis that good governance has positive effects on economic growth, and exploring whether passive governance, characterised by less extensive regulations, is more compatible with economic growth than active governance, which is characterised by more extensive regulations. The analysis employs multiple fixed-effects panel regression models on data from 15 Latin American countries over 2002-2022 and uses the Regulatory Quality index from World Governance Indicators (WGI) and Fraser Institute´s regulatory intensity index to proxy for governance. The results reveal no statistically significant effects of government effectiveness on economic growth and no evident advantage of passive or active governance styles. These findings indicate that governance, measured by the WGI or Fraser Institute´s index, might play a less important role in determining Latin American economic growth.